2009
DOI: 10.1093/ejechocard/jep151
|View full text |Cite
|
Sign up to set email alerts
|

European Association of Echocardiography recommendations for training, competence, and quality improvement in echocardiography

Abstract: The main mission statement of the European Association of Echocardiography (EAE) is 'to promote excellence in clinical diagnosis, research, technical development, and education in cardiovascular ultrasound in Europe'. As competence and quality control issues are increasingly recognized by patients, physicians, and payers, the EAE has established recommendations for training, competence, and quality improvement in echocardiography. The purpose of this document is to provide the requirements for training and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0
20

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 27 publications
0
122
0
20
Order By: Relevance
“…Both cardiologists worked on the same machine; therefore, technical sensitivity was always identical throughout the study. Standardized operating procedures were used based on international guidelines (40) and monthly meetings were conducted for quality control. The echocardiographic quantitative assessment was performed according to standard methods (41).…”
Section: Echocardiographic Studymentioning
confidence: 99%
“…Both cardiologists worked on the same machine; therefore, technical sensitivity was always identical throughout the study. Standardized operating procedures were used based on international guidelines (40) and monthly meetings were conducted for quality control. The echocardiographic quantitative assessment was performed according to standard methods (41).…”
Section: Echocardiographic Studymentioning
confidence: 99%
“…En Europa se han publicado estándares para la solicitud del ecocardiograma transtorácico, la a c r e d i t a c i ó n d e l o s l a b o r a t o r i o s d e ecocardiografía y en el 2003 se realizaron los primeros exámenes de acreditación para los individuos entrenados que efectúan y reportan los exámenes ecocardiográficos, originando como misión de la sociedad Europea de Cardiología y Ecocardiografía "promover la excelencia en el diagnóstico clínico, investigación, desarrollo técnico y educación en ultrasonido cardiovascular en (4,5) Europa" . Las recomendaciones para el ecocardiograma transtorácico incluye el que sea realizado por un especialista o personal de salud con entrenamiento en ecocardiografía y se han establecido guías y sistemas de auditoria para revisar las solicitudes, reportes e historias clínicas de acuerdo a los hallazgos del ecocardiograma.…”
Section: Discussionunclassified
“…21 The experienced echocardiographer will generally use the two techniques (TTE and TOE) interchangeably in order to obtain the information required. The operator must take into account the pathophysiological status of the patient, frequently with rapidly changing haemodynamic support, and synthesize all information to provide the relevant guidance to the attending physician.…”
Section: Level Of Competencementioning
confidence: 99%
“…The operator must take into account the pathophysiological status of the patient, frequently with rapidly changing haemodynamic support, and synthesize all information to provide the relevant guidance to the attending physician. For performing TOE studies and advanced echocardiography techniques, operators should fulfil advanced echocardiography training requirements 21 and undergo specialized additional training in undertaking studies in the acute setting. Since echocardiographic examinations in patients with an acute cardiovascular condition are frequently requested as urgent/ emergency, it is suggested that all such studies should be supervised by an expert cardiologist with an advanced level of competence in echocardiography 19,21 and experienced in performing and interpreting echocardiography in the acute/ critical care setting.…”
Section: Level Of Competencementioning
confidence: 99%